Recognizing potential of LiDAR for comprehensive measurement of sea spray flux for improving the prediction of marine icing in cold conditions - A review - Dhar, Sushmit; Khawaja, Hassan Abbas (Ocean engineering, 2021)
Marine icing phenomenon depends on multiple variables like vessel characteristics and uncertain factors like environmental parameters, developing an accurate model for its forecasting, evaluation, and estimation is very challenging. Commonly, most severe ice accretion is caused due to sea spray. The past attempts to measure impinging sea spray flux were carried out on specific parts of the spray cloud, and most of the empirical spray-flux expressions presented only work in specific conditions. This necessitates further real-time and accurate field measurements of the entire impinging spray flux carried out in multiple scenarios in order to develop more practical correlation. High temporal and spatial resolution measurements and scanning ability of the LiDAR technique has proven to be useful in the agricultural domain for studying pesticide spray drift. This work reviews the past studies carried out using LiDAR technique for measuring the evolution of the pesticide spray cloud, asserting the potential of using a shipborne LiDAR for analysing sea spray in the study of marine icing phenomenon. The LiDAR system is capable to visualise the evolution of the sea spray drift with a high spatial and temporal resolution, which can enable comprehensive real-time measurement of spray flux for the entire sea spray cloud. •Primary objectives:1.Detailing the complexity of marine icing phenomenon.2.Need for comprehensive real time measurement of the spray cloud.3.Proposing LiDAR as a potential technology solution for accurate measurement of sea spray.•Secondary objectives:1.Reviewing past efforts in the subject domain of marine icing.2.Reviewing potential of LiDAR technology in measuring 2D/3D particles fluxes.3.Near-range measurements using LiDAR.4.Subsequent research to design and develop a shipborne LiDAR for measuring sea spray.